The eclipse java metamodel scaffolding software engineering research on java projects with MDE techniques - Coimbra, P. (2022)
Java on the Eclipse IDE is a frequent choice for software development nowadays. Software Engineering researchers have built program analysis tools in that environment for several purposes. However, that requires a deep understanding of Eclipse internals, such as the Java AST. This paper discusses the feasibility of a metamodel-driven approach to scaffold the construction of such tools. Its core is the Eclipse Java Metamodel (EJMM), obtained through reverse engineering. The latter is instantiated with meta-objects representing the constructs of a given Java program. We then use OCL to traverse programs very easily. To validate the feasibility of our metamodel-driven approach to program analysis, we developed an Eclipse plug-in based on it, to support the metamodel-driven measurement (M2DM) approach.